2019
DOI: 10.1002/pd.5409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the post‐LA space index in the normal fetus

Abstract: Objective We previously reported the post‐LA space index (PLAS index), which is calculated as left atrial‐descending aorta distance (LD) divided by the diameter of descending aorta (DA), could be useful for prenatal diagnosis of total anomalous pulmonary venous connection (TAPVC). In this study, we evaluated PLAS index in normal fetuses to assess its usefulness. Methods In 304 normal fetuses, LD and DA were retrospectively measured, and the PLAS index was calculated. In 206 fetuses with data on the biparietal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 11 publications
3
22
1
Order By: Relevance
“…7 In their following study, they found that the optimal cutoff value of the PLAS index was 1.17, with the sensitivity and specificity both being 100%. 4 They suggested that if the cutoff value is set at 1.0, the sensitivity would be 100% in both studies, with specificity of 89% and 93%, respectively. This suggests that determining whether the distance behind the LA is wider than the DA may be a simple method for detecting cardiac abnormalities.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…7 In their following study, they found that the optimal cutoff value of the PLAS index was 1.17, with the sensitivity and specificity both being 100%. 4 They suggested that if the cutoff value is set at 1.0, the sensitivity would be 100% in both studies, with specificity of 89% and 93%, respectively. This suggests that determining whether the distance behind the LA is wider than the DA may be a simple method for detecting cardiac abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported changes in the PLAS in fetal CHDs, especially for the prenatal diagnosis of a TAPVC. 4,5,7,12 Valsangiacomo et al 12 reported that a separation between the posterior wall of the atrium and the descending aorta was observed in fetuses with TAPVC. Berg et al 5 suggested that an abnormality in the area behind the heart on fetal echocardiography is an important clue when screening for fetal CHDs, including TAPVC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations